Virtual and augmented reality: New tools for visualizing, analyzing, and communicating complex morphology. (2nd November 2021) - Cieri, Robert L.; Turner, Morgan L.; Carney, Ryan M.; Falkingham, Peter L.; Kirk, Alexander M.; Wang, Tobias; Jensen, Bjarke; Novotny, Johannes; Tveite, Joshua; Gatesy, Stephen M.; Laidlaw, David H.; Kaplan, Howard; et al.
Abstract: Virtual and augmented reality (VR/AR) are new technologies with the power to revolutionize the study of morphology. Modern imaging approaches such as computed tomography, laser scanning, and photogrammetry have opened up a new digital world, enabling researchers to share and analyze morphological data electronically and in great detail. Because this digital data exists on a computer screen, however, it can remain difficult to understand and unintuitive to interact with. VR/AR technologies bridge the analog‐to‐digital divide by presenting 3D data to users in a very similar way to how they would interact with actual anatomy, while also providing a more immersive experience and greater possibilities for exploration. This manuscript describes VR/AR hardware, software, and techniques, and is designed to give practicing morphologists and educators a primer on using these technologies in their research, pedagogy, and communication to a wide variety of audiences. We also include a series of case studies from the presentations and workshop given at the 2019 International Congress of Vertebrate Morphology, and suggest best practices for the use of VR/AR in comparative morphology. Abstract : Virtual and augmented reality (VR/AR) will revolutionize the study of morphology by making interactions with digital data nearly as intuitive, meaningful, and accessible as handling real biological structures. VR/AR also provides for additional immersive experiences and enables digital explorations not possible on analog specimens. This manuscript describes VR/AR hardware, software, and techniques, and is designed to give practicing morphologists and educators a primer on using these technologies in their research, pedagogy, and communication to a wide variety of audiences.